2010
DOI: 10.1089/end.2009.0463
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Intracorporeal Hand-Sewn Bowel Anastomosis During Pediatric Bladder Reconstructive Surgery

Abstract: Bowel anastomosis performed during robot-assisted laparoscopic surgery in both adult and pediatric populations has typically been performed using endoscopic staplers or with exteriorization of the bowel. In the pediatric population, no articles have been published that explore the possibility of a completely intracorporeal hand-sewn anastomosis during robot-assisted laparoscopic surgery. We report our series of six children who were undergoing robot-assisted laparoscopic intracorporeal hand-sewn bowel anastomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…(iv) Does it have any advantages compared with its predecessor? We have previously shown that complete intracorporeal robotic‐assisted laparoscopic bowel anastomosis in children undergoing bladder reconstructive surgery is a feasible procedure [13]. This series builds on our previous experience, and applies it towards complete intracorporeal RALIMA.…”
Section: Discussionmentioning
confidence: 88%
“…(iv) Does it have any advantages compared with its predecessor? We have previously shown that complete intracorporeal robotic‐assisted laparoscopic bowel anastomosis in children undergoing bladder reconstructive surgery is a feasible procedure [13]. This series builds on our previous experience, and applies it towards complete intracorporeal RALIMA.…”
Section: Discussionmentioning
confidence: 88%
“…Gundeti et al . in 2010 reported a successful series of completely intracorporeal reconstruction, showing also advantages in recuperation.…”
Section: Discussionmentioning
confidence: 99%
“…In that experimental cohort extracorporeal bowel anastomosis was pursued to avoid anastomotic leak. Gundeti et al [3] in 2010 reported a successful series of completely intracorporeal reconstruction, showing also advantages in recuperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the right side an inferior working port with a superior 12 mm assistant port for which a laparoscopic bowel stapler can be passed, however a robotic hand-sewn bowel anastomosis is also possible as described by Gundetti et al. [55] . Ileocystoplasty is usually performed with a concomitant catheterizable channel, and bilateral extravesical reimplantations with good postoperative results [56] .…”
Section: Surgeriesmentioning
confidence: 99%